Bacterial Communities Associated with the Roots of Typha spp. and Its Relationship in Phytoremediation Processes - Martínez-Martínez, Joana Guadalupe; Rosales-Loredo, Stephanie; Hernández-Morales, Alejandro; Arvizu-Gómez, Jackeline Lizzeta; Carranza-Álvarez, Candy; Macías-Pérez, José Roberto; Rolón-Cárdenas, Gisela Adelina; Pacheco-Aguilar, Juan Ramiro (Microorganisms (Basel), 2023)
Heavy metal pollution is a severe concern worldwide, owing to its harmful effects on ecosystems. Phytoremediation has been applied to remove heavy metals from water, soils, and sediments by using plants and associated microorganisms to restore contaminated sites. The Typha genus is one of the most important genera used in phytoremediation strategies because of its rapid growth rate, high biomass production, and the accumulation of heavy metals in its roots. Plant growth-promoting rhizobacteria have attracted much attention because they exert biochemical activities that improve plant growth, tolerance, and the accumulation of heavy metals in plant tissues. Because of their beneficial effects on plants, some studies have identified bacterial communities associated with the roots of Typha species growing in the presence of heavy metals. This review describes in detail the phytoremediation process and highlights the application of Typha species. Then, it describes bacterial communities associated with roots of Typha growing in natural ecosystems and wetlands contaminated with heavy metals. Data indicated that bacteria from the phylum Proteobacteria are the primary colonizers of the rhizosphere and root-endosphere of Typha species growing in contaminated and non-contaminated environments. Proteobacteria include bacteria that can grow in different environments due to their ability to use various carbon sources. Some bacterial species exert biochemical activities that contribute to plant growth and tolerance to heavy metals and enhance phytoremediation.